Luminosity levels and substrates composition on Bermuda Grass development - Amaral, Joao Andre do; Pagliarini, Maximiliano Kawahata; Haga, Kuniko Iwamoto [UNESP]; Monteiro de Castilho, Regina Maria [UNESP] (Soc Brasileira Floricultura & Plantas Ornamentais, 2019)
Turfgrass is a fundamental part in sports fields' composition. Some aspects should be taken into account in the choosing species process, such as turfgrass use (trampling tolerance), turfgrass management, physical-chemical soil conditions and shade tolerance. With accomplishment of sporting events in Brazil, there was requirement for football arenas reform and modernization. Among architecture alterations, coverings implantation was noticed, resulting luminosity reduction affecting turfgrass development. Therefore, the objective of this work was to evaluate the influence of luminosity and substrates on Bermuda grass (Cynodon dactylon x C. ttrmsvaalensis) development. The experiment was conducted in a 5 x 4 factorial scheme (substrates x luminosities), in completely randomized design with 20 treatments and 3 replicates. The substrates were: S1 = Soil, S2 = Soil + sand (2:1), S3 = Soil + organic matter (1:1), S4 = Soil + organic matter + sand (2:1:1) and S5 = organic matter + sand (3:1), in four luminosity conditions: full sun, 30%, 50% and 80% of shading for six months. We evaluated substrates fertility composition, solar radiation, grass height and fresh and dry mass. Shading interfered on Bermuda grass development, which tolerates intermediate shading (30% and 50%). Substrates containing the highest levels of organic matter submitted to shading had impaired turfgrass performance.
Keywords: Cynodon dactylon x C. transvaalensis; Turfgrass; shade tolerance; sport fields; organic matter